2000
DOI: 10.1002/1098-2345(200011)52:3<115::aid-ajp1>3.0.co;2-z
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of social status in cynomolgus monkeys (Macaca fascicularis) after group formation

Abstract: The purpose of the present study was to determine whether various behavioral and hormonal markers obtained in individually housed monkeys would be predictive of social rank following group housing. Body weight, serum cortisol and testosterone levels, and locomotor activity in an open‐field apparatus were examined in 20 experimentally naive male cynomolgus monkeys (Macaca fascicularis) while they were individually housed. It was hypothesized that eventual subordinate monkeys would have higher cortisol levels an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
62
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 86 publications
(72 citation statements)
references
References 38 publications
9
62
1
Order By: Relevance
“…There was more variance in body mass measures and T3 concentrations in l/l females compared to svariant females at baseline when social ranks were similar. Body weight has been shown to be a predictor of eventual dominant status in some reports [81] but not others [Bastian, 2003No. 1810, suggesting that appreciably larger animals may elicit submissive responsiveness from smaller cage mates.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There was more variance in body mass measures and T3 concentrations in l/l females compared to svariant females at baseline when social ranks were similar. Body weight has been shown to be a predictor of eventual dominant status in some reports [81] but not others [Bastian, 2003No. 1810, suggesting that appreciably larger animals may elicit submissive responsiveness from smaller cage mates.…”
Section: Discussionmentioning
confidence: 99%
“…1810, suggesting that appreciably larger animals may elicit submissive responsiveness from smaller cage mates. One study [81] also found that greater reactivity to a novel environment predicted subordinate status. The significance of this observation for the present study is data showing thyroid hormones are lower in a number of affective disorders [82][83][84] and T3 can improve performance in novel, fear-evoking tasks by direct action on the hippocampus [85].…”
Section: Discussionmentioning
confidence: 99%
“…Although the literature suggests that certain endocrine parameters, for example high plasma testosterone levels, may predispose an animal to express higher levels of aggression and become DOM, this is not universally the case. Likewise there is no effect of pre-grouping on the basis of the response to a dexamethasone challenge, plasma cortisol, or plasma testosterone in primates [40][41][42]. However, in the Common marmoset (Callithrix jacchus) cortisol concentrations in females prior to group formation are predictive of social status.…”
Section: Potential Predictors Of Social Statusmentioning
confidence: 99%
“…This body weight bias is also apparent in colony models where it can serve as a predicting factor in determining dominance [40]. Because of this, animals used in the VBS are typically weight-matched before the colony is formed such that no individual animal has a significant weight advantage thereby allowing us to consider other factors in determining dominance and subordination.…”
Section: Potential Predictors Of Social Statusmentioning
confidence: 99%
“…Thus, while there are few changes in brain serotonergic activity following a second interaction with a familiar opponent, those that occur do not appear to be increases stimulated by a second stressful social interaction, but rather are represented by reductions in serotonergic activity, modulated by visual sign stimuli (raphé) and previous social status (hippocampal CA 3 ) respectively [39]. Dopaminergic activity is also influenced by social status and social interactions [3,17,32,51,84]. Dopaminergic activity in hippocampal nuclei of various vertebrate species has also been shown to be critical for spatial memory formation and retrieval [61,81].…”
Section: Central Monoaminergic Response To a Second Social Interactionmentioning
confidence: 99%